2019
DOI: 10.1073/pnas.1917762116
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale porous elastomer substrates for multifunctional on-skin electronics with passive-cooling capabilities

Abstract: In addition to mechanical compliance, achieving the full potential of on-skin electronics needs the introduction of other features. For example, substantial progress has been achieved in creating biodegradable, self-healing, or breathable, on-skin electronics. However, the research of making on-skin electronics with passive-cooling capabilities, which can reduce energy consumption and improve user comfort, is still rare. Herein, we report the development of multifunctional on-skin electronics, which can passiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(138 citation statements)
references
References 56 publications
2
127
0
Order By: Relevance
“…For example, high water vapor permeability is achieved by processing the electrodes into a suitable porous shape or by fabricating electrodes on a porous substrate. [ 16‐21 ] Since these electrodes are less likely to inhibit water evaporation from skin, it is expected that measurements could be performed in a nearly natural state without causing skin dampness by wearing them. In addition, there are reports on electrodes that use highly biocompatible materials such as poly‐vinyl‐alcohol (PVA), [ 18,21 ] gels, [ 22 ] and silk fibroin for biocompatibility.…”
Section: Electrode Conductivity [S M−1] Thickness [µM] Water Vapor Pementioning
confidence: 99%
“…For example, high water vapor permeability is achieved by processing the electrodes into a suitable porous shape or by fabricating electrodes on a porous substrate. [ 16‐21 ] Since these electrodes are less likely to inhibit water evaporation from skin, it is expected that measurements could be performed in a nearly natural state without causing skin dampness by wearing them. In addition, there are reports on electrodes that use highly biocompatible materials such as poly‐vinyl‐alcohol (PVA), [ 18,21 ] gels, [ 22 ] and silk fibroin for biocompatibility.…”
Section: Electrode Conductivity [S M−1] Thickness [µM] Water Vapor Pementioning
confidence: 99%
“…also proposed a phase separation‐controlled synthesis method to prepare multiscale porous electrode substrate. [ 13 ] During this process, polystyrene‐ block ‐poly(ethylene‐ran‐butylene)‐ block ‐polystyrene (SEBS) and isopropyl alcohol (IPA) were mixed into chloroform to fabricate the precursor solution. Subsequently, the precursor was coated on an aluminum foil and dried in ambience.…”
Section: Breathabilitymentioning
confidence: 99%
“…[ 9,10 ] As an index of the initiation and fatigue of activated muscles, EMG signals originate from electrical activities produced by muscle of interest and are suitable for monitoring muscular diseases and mental fatigue etc. [ 11 ] Particularly, the characteristics of EMG signals from muscles on forearm can be directly correlated to hand gestures, [ 12 ] therefore, EMG signals are widely used for gesture recognition, [ 13 ] prosthetic control, [ 14 ] etc. EEG signals obtained from human scalp surface capture the post‐synaptic potentials generated by pyramidal neurons, [ 15 ] thus can be utilized to assist brain‐activity cognition and mental disease diagnosis, such as epilepsy diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…118 Prasher et al found an optimal volume fraction for a given pressure and filler shape. 115 Xu et al 119 introduced a substrate, namely, multiscale porous polystyrene-block-poly(ethylene-ran-butylene)-blockpolystyrene (SEBS), to support the cooling effect. They developed multifunctional on-skin electronics with improved passive cooling capability that can deliver 6 C of cooling effects under a solar intensity of 840 W.m −2 .…”
Section: Advanced Materials In Fabricationmentioning
confidence: 99%